Was the Asian crisis a wake-up call?: Foreign reserves as self-protection - Mendoza, Ronald U (Archīum Ateneo, 2010)
Digging deeper into the self-protection rationale for holding reserves, this paper examines the empirical link between reserve holding patterns and crisis vulnerability, comparing the pre- and post-Asian crisis periods, and across different groups of developing countries. Analyzing data for 51 developing countries during the period 1982–2004, this paper finds evidence that the elasticity of developing country reserves with respect to certain crisis vulnerability indicators like foreign debt service and total external liabilities seems to be higher in the post-Asian crisis period, suggesting that policymakers’ precautionary responsiveness by holding more reserves has increased. Grouping countries according to their type of vulnerability (commodity, debt or sudden stop related), countries prone to sudden stops in capital inflows also seem to have adjusted their policies the most towards higher precautionary reserve holding. Furthermore, from the point of view of self-protection, China's reserve holding patterns appear consistent with what developing countries more generally seem to be undertaking.